2015
DOI: 10.5312/wjo.v6.i1.62
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic foot syndrome: Immune-inflammatory features as possible cardiovascular markers in diabetes

Abstract: Diabetic foot ulcerations have

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
90
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(127 citation statements)
references
References 100 publications
(140 reference statements)
7
90
0
4
Order By: Relevance
“…T2DM as a chronic inflammatory state is accompanied by a number of metabolic disturbances. The majority of diabetic patients with DFU present hyperglycemia, insulin resistance, and dyslipidemia which lead to the development and progression of further complications . In the current study, we observed that magnesium and vitamin E co‐supplementation provided a significant improvement in ulcer length, width and depth.…”
Section: Discussionsupporting
confidence: 56%
“…T2DM as a chronic inflammatory state is accompanied by a number of metabolic disturbances. The majority of diabetic patients with DFU present hyperglycemia, insulin resistance, and dyslipidemia which lead to the development and progression of further complications . In the current study, we observed that magnesium and vitamin E co‐supplementation provided a significant improvement in ulcer length, width and depth.…”
Section: Discussionsupporting
confidence: 56%
“…Hyperglycemia and insulin resistance are associated with an acceleration of arteriosclerotic changes of the greater arteries resulting in decreased blood flow, further contributing to a limb threatening ischemic condition . The diabetic dyslipidemia is one of several factors that contribute to developing macrovascular disease in diabetic patients . Zinc intake may improve parameters of glucose homeostasis through the synthesis, storage, and secretion of monomeric insulin, as well as conversion to dimeric form for storage and secretion as crystalline insulin and participation in insulin action and carbohydrate metabolism .…”
Section: Discussionmentioning
confidence: 99%
“…A major complication of both type 1 and type 2 diabetes is foot ulceration, and evidence is now emerging to show that diabetes with foot ulceration portends an even higher mortality rate than diabetes alone . This excess mortality remains even after adjusting for chronic kidney disease and known cardiovascular comorbidities .…”
Section: Introductionmentioning
confidence: 99%